The State of the Immune Status in Rheumatoid Artritis. (Eurasian Medical Research Periodical, 2022)
A review of the literature on the prognosis of rheumatoid arthtitis, its inflammatory autoimmune disease with articular and systemic effects. Its exact cause is unknown, but genetic and environmental factors are contributory. T cells, B cells. Joint damage begins at the synovial membrane, where the influx and/or local activation of mononuclear cells and the formation of new blood vessels cause synovitis. Antigen-activated CD4(+) T cells amplify the immune response by stimulating other mononuclear cells, synovial fibroblasts, chondrocytes and osteoclasts. Several types of immunomodulatory molecules, mainly cytokines secreted by immune cells, mediate the pathogenesis of RA. Sensitive biomarkers are critical for early detection of disease, as well as for monitoring disease activity and progression. This review aims to discuss the pathogenic role of various immune cells and immunological molecules in RA.